Methodology to quantify the ratio of multiple-to single-charged fractions acquired in aerosol neutralizers. Issue 4 (2nd April 2016) - Mamakos, Athanasios
ABSTRACT: A methodology for the quantification of the ratio of multiple- to single-charged fractions acquired in aerosol neutralizers is presented. These quantities are necessary for an accurate monodisperse calibration of aerosol instrumentation. A tandem Differential Mobility Analyzer (DMA) setup is required, with the second DMA scanning the electrical mobility spectra classified in the first DMA. In contrast to previous studies on the quantification of bipolar charge distribution utilizing tandem DMA schemes, the methodology targets at the direct determination of the multiple- to single-charge fractions and does so through the analysis of the raw signal instead of the inverted size distributions, thus circumventing errors associated with the assumptions in the DMA data inversion. The proposed methodology is employed for the characterization of different types of aerosols commonly employed for instrument calibration. Spherical liquid particles (emery oil and dioctyl sebacate) were found to acquire lower multiple charge fractions than those suggested by the commonly employed regression fits of Wiedensohler, which was published in the year 1988 in the Journal of Aerosol Science (vol. 19, pp. 387–389), but still within the range of values reported in the literature. Diffusion flame soot and spark generated graphite particles, produced by a miniCAST 6203C burner and a PALAS DNP 3000, respectively, exhibited higher fraction of multiple charges, in good agreement with previous work on agglomerates. The use of a soft X-ray bipolar charger (TSI 3088) yielded systematically higher multiple fractions of positive charges compared to a 85 Kr neutralizer (TSI 3077A), confirming the importance of direct photoionization charging on the former. Copyright © 2016 American Association for Aerosol Research